Cost-Effectiveness of Primary and Revision Surgery for Adult Spinal Deformity. Issue 11 (1st June 2018) - Raman, Tina; Nayar, Suresh K.; Liu, Shuiqing; Skolasky, Richard L.; Kebaish, Khaled M.
Abstract : Study Design: Retrospective comparative study. Objective: The purpose of this study is to compare functional outcomes, hospital resource utilization, and spine-related costs during 2 years in patients who had undergone primary or revision surgery for adult spinal deformity (ASD). Summary of Background Data: After surgery for ASD, patients may require revision for pseudarthrosis, implant complications, or deformity progression. Data evaluating cost-effectiveness of primary and, in particular, revision surgery, for ASD are sparse. Methods: We retrospectively reviewed records for 119 consecutive patients who had undergone primary or revision surgery for ASD. Two-year total spine-related medical costs were derived from hospital charge data. Functional outcome scores were extracted from prospectively collected patient data. Cost utility ratios (cost/quality-adjusted life-year [QALY]) at 2 years were calculated and assessed against a threshold of $154, 458/QALY gained (three times the 2015 US per-capita gross domestic product). Results: The primary surgery cohort (n = 56) and revision cohort (n = 63) showed significant improvements in health-related quality-of-life scores at 2 years. Median surgical and spine-related 2-year follow-up costs were $137, 990 (interquartile range [IQR], $84, 186) for primary surgery and $115, 509 (IQR, $63, 753) for revision surgery and were not significantly different between the two groups ( P  = 0.12). We report 2-year QALY gains of 0.36 in the primary surgery cohort and 0.40 in the revision group ( P  = 0.71). Primary instrumented fusion was associated with a median 2-year cost per QALY of $197, 809 (IQR, $187, 350) versus $129, 950 (IQR, $209, 928) for revision surgery ( P  = 0.31). Conclusion: Revision surgery had lower total 2-year costs and higher QALY gains than primary surgery for ASD, although the differences were not significant. Although revision surgery for ASD is known to be technically challenging and to have a higher rate of major complications than primary surgery, revision surgery was cost-effective at 2 years. The cost/QALY ratio for primary surgery for ASD exceeded the threshold for cost effectiveness at 2 years. Level of Evidence: 3